Effect of Chronic Domperidone Use on QT Interval: A Large Single Center Study. Issue 9 (October 2019) - Field, Justin; Wasilewski, Melissa; Bhuta, Rajiv; Malik, Zubair; Cooper, Joshua; Parkman, Henry P.; Schey, Ron
Abstract : Goals: The goal of this study was to determine the effect and safety of domperidone on QTc interval at the commonly prescribed doses of 30 to 80 mg daily. Background: Domperidone is a dopamine receptor antagonist used for the treatment of gastroparesis. However, it has been associated with QT prolongation, ventricular arrhythmias, and sudden cardiac death. Study: This study analyzed patients prescribed domperidone for treatment of gastroparesis between January 2012 and September 2017 at a single center. This study reviewed EKGs, primarily the QTc interval, taken at baseline, 2 to 6 months after initiation of domperidone, 6 to 12 months after initiation, and ≥12 months after initiation. Concurrent QTc prolonging medications were recorded for each patient. The primary endpoint was QTc prolongation >500 ms. Secondary endpoints were QTc >450 ms for males, a QTc>470 ms for females, QTc prolongation ≥20 ms above baseline, and QTc prolongation >60 ms above baseline. Results: In total, 246 patients were included for analysis (age, 46.3±17.4 y; F 209). EKGs were available for all 246 patients before treatment, 170 patients at 2 to 6 months, 135 at 6 to 12 months, and 152 patients at least 1 year after domperidone initiation. Of 246 subjects, 15 patients (6.1%, 9 female) had clinically important QTc prolongation; 11 had QTc >450 ms for males or >470 ms for females; none had QTc prolongation >500 ms; 5 (2.0%) had >60 ms over baseline and 61 (24.7%) patients had QTc increase of ≥20 ms but <60 ms from baseline. Conclusions: Domperidone at the conventionally used doses to treat gastroparesis (30 to 80 mg/d) was associated with QTc prolongation in only 6% of patients with no QT interval reaching the point considered to be clinically significant. These data suggest that domperidone can be safely prescribed at doses of 30 to 80 mg daily for the treatment of gastroparesis.